1986
DOI: 10.1111/j.1365-2818.1986.tb02726.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of frozen sections relevant to quantitative microanalysis

Abstract: SUMMARY Difficulties in the quantitative X‐ray microanalysis of frozen sections may conceivably arise from ice‐crystal damage and from electron‐beam damage. X‐ray peak‐to‐continuum ratios are commonly taken as a quantitative index of elemental concentrations. But recent reports suggest that in dehydrated frozen sections such ratios vary greatly with the scale of ice‐crystal formation existing prior to sublimation. The experiments in these reports are re‐interpreted here; it is argued that peak intensities may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Similar observations were reported by Wendt-Gallitelli and Wolburg (1984). Hall (1986b) ascribes this effect to inappropriate correction for extraneous background. Nevertheless, the size of the ice crystal segregation zones has to be considered as a possible source of error in the evaluation of X-ray microanalytical data.…”
Section: Mass Loss Of a Frozen-hydrated Cryosection Of Yeastsupporting
confidence: 83%
“…Similar observations were reported by Wendt-Gallitelli and Wolburg (1984). Hall (1986b) ascribes this effect to inappropriate correction for extraneous background. Nevertheless, the size of the ice crystal segregation zones has to be considered as a possible source of error in the evaluation of X-ray microanalytical data.…”
Section: Mass Loss Of a Frozen-hydrated Cryosection Of Yeastsupporting
confidence: 83%
“…For example, the carbon in carrageenan was lost with a rate given by 0, = 50e/A' (5 x lo3 e/nm') at 300K but 0, = 670e/A2 (6.7 x lo4 elm') at 100 K. For the nitrogen in nitrocellulose, 0, was 14.4 e/A2 (140 e/nm') at 300K and 17e/A2 (1700e/nm2) at 100K. Similar effects were seen by X-ray spectroscopy (Cantino et al, 1986;Hall, 1986). Other laboratories (Isaacson et al, 1978;Leapman, 1982;Vesely, 1984) have shown a reduction in fluorine concentrations due to electron irradiation, but more recent studies have discovered some more stable fluorine compounds (Ciliax et al, 1990).…”
Section: S T a B I L I Z A T I O N O F S P E C I F I C E L E M E N T Ssupporting
confidence: 58%
“…Although much of the quantitative techniques in biological X-ray microanalysis were established during the seventies, the field still is in an active state of development. Areas in which progress is being made or expected are mainly a) more accurate determination of local mass either with the use of the corrected continuum signal or by alternative techniques (Hall, 1986), b) quantitative analysis of light (Z < 11) elements, and c) determination of the local water content. In addition, increased computer power has opened possibilities for fully quantitative mapping, where quantitative analysis is carried out on each pixel of the X-ray map (see, e.g., Fiori, 1986; Heyman and Saubermann, 1987; Saubermann and Heyman, 1987;Somlyo et al, 1986).…”
Section: Current Developmentsmentioning
confidence: 99%